2021
DOI: 10.1177/08850666211015595
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ultrasound Guided Gastrostomy Tube Placement: A Prospective Cohort Trial

Abstract: Background: To compare the safety and efficacy of percutaneous ultrasound guided gastrostomy (PUG) tube placement with traditional fluoroscopic guided percutaneous gastrostomy tube placement (PRG). Methods: A prospective, observational, non-randomized cohort trial was performed comparing 25 consecutive patients who underwent PUG placement between April 2020 and August 2020 with 25 consecutive patients who underwent PRG placement between February 2020 and March 2020. Procedure time, sedation, analgesia requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Most importantly, PUG is at least as safe as percutaneous endoscopic gastrostomy (PEG) and percutaneous radiologic gastrostomy (PRG). Two prospective studies (n=50) have shown an equivalent safety profile compared to matched retrospective cohorts (3,4). Critical care teams have demonstrated decreased time to gastrostomy placement for their patients when compared to PEG, decreased ICU length of stay (LOS) and immense utility in the COVID-19 pandemic (5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, PUG is at least as safe as percutaneous endoscopic gastrostomy (PEG) and percutaneous radiologic gastrostomy (PRG). Two prospective studies (n=50) have shown an equivalent safety profile compared to matched retrospective cohorts (3,4). Critical care teams have demonstrated decreased time to gastrostomy placement for their patients when compared to PEG, decreased ICU length of stay (LOS) and immense utility in the COVID-19 pandemic (5)(6)(7).…”
mentioning
confidence: 99%
“…Meeting this care demand requires a safe approach, ubiquitous to all critical care environments and critical care physicians. Point of care ultrasound is the optimal choice, as it has been safely utilized in both bedside tracheostomy and gastrostomy (3,4,6,7,9). When appropriately indicated, based upon current literature, PUG or TPUG can serve as a primary option for safe and timely care for your critically ill patients.…”
mentioning
confidence: 99%
“…In the published studies of PUG, they had to use fluoroscopy as a bail out in significant number of patients. Furthermore, majority of the procedures were done in the interventional radiology (IR) suite and only a small number of patients underwent a true bedside gastrostomy in ICU (3)(4)(5)(6). Given the low number of PUG procedures performed in the ICU we cannot comment or extrapolate the conclusions on ICU-specific outcomes.…”
mentioning
confidence: 99%
“…This disputes the whole purpose of the concept of combined tracheostomy Letter to the Editor Response to the author on "Percutaneous Ultrasound Gastrostomy (PUG) overview updates" in response to our review on "An overview of percutaneous endoscopic gastrostomy (PEG) tube placement in the intensive care unit (ICU)'' and gastrostomy in a single setting in ICU. In addition, PUG was performed by interventional radiologists with extensive expertise and experience in diagnostic ultrasound and percutaneous ultrasound-guided procedures (5,6). The study quoted by the authors on critical care physicians performing PUG is a very small study of five patients and cannot be used as a generalized measure without robust data and outcomes study with large patient population (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation